DEVELOPMENT OF SEMANTIC DOCUMENT REPOSITORY PROTOTYPE AND ITS INTEGRATION WITH DISTRIBUTED ONTOLOGICAL PORTAL FOR EDUCATION AND RESEARCH RESOURCES OF MES OF UKRAINE MANAGEMENT - N.V. Ryabova; O.Y. Shevchenko; M.V. Biloivanenko; G.A. Voskoboynykova; M.V. Golovianko; N.O. Voloshyna; O.V. Shubkina (Kherson State University, 2010)
The notion of a semantic repository in modern systems of knowledge management is considered in this article. The hardware-software architecture of secure semantic repository of documents with the ability to version control is proposed. Also, its integration with distributed ontological portal for management education and research resources of MESU is considered.